(untitled) (Journal of Shaheed Suhrawardy Medical College, 2019)
Aim: To evaluate the treatment outcome of Philos plate fixation for displaced proximal humeral fractures in 17 patients. Methods: This was a prospective study with 17 patients, 11 women, 6 men with average age 62yr having displaced proximal humeral fractures fixed with Philos plate. All the fractures were closed and no associated injuries, classified as 2 part (n=12),3 part (n=3),4part (n=2) according to Neer classification. All patients were evaluated clinically, functionally and radiologically using the Constant Shoulder Score. Results: Patients were followed up for 6 to 24 months. All the fractures healed except one which was four part fracture in 65yr woman. The fracture was in varus position and screw penetration of humeral head at six week. Revision surgery was done and eventually fracture united. Conclusion: Philos plate fixation is a good stable construct with minimal metal work problems and permit early movement J Shaheed Suhrawardy Med Coll, December 2018, Vol.10(2); 80-82